1992
DOI: 10.1152/ajpregu.1992.263.3.r647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise in hypobaric conditions on atrial natriuretic peptide secretion

Abstract: To evaluate the role of atrial natriuretic peptide (ANP) in exercise-related cardiovascular and hormonal adjustments in hypobaric conditions, 14 young athletes performed a maximal ergometer test in a hypobaric chamber adjusted to simulate the altitudes of sea level and 3,000 m. Plasma immunoreactive ANP levels rose from 5.89 to 35.1 pmol/l at sea level and rose significantly less (P less than 0.05), from 5.36 to 22.3 pmol/l, at simulated 3,000 m. Plasma immunoreactive amino-terminal peptide of proANP (NT-proAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 0 publications
2
62
1
1
Order By: Relevance
“…Objective To determine whether low cardiovascular profile (CVP) (28 (range, 24-35) weeks vs. 35 (range, 26-40) weeks, P < 0.01) and had lower CVP scores (4 (range,[2][3][4][5][6][5][6][7][8][9][10], P < 0.0001). All CVP subscale scores were lower (P < 0.01) in Group 1 than in Group 2 fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Objective To determine whether low cardiovascular profile (CVP) (28 (range, 24-35) weeks vs. 35 (range, 26-40) weeks, P < 0.01) and had lower CVP scores (4 (range,[2][3][4][5][6][5][6][7][8][9][10], P < 0.0001). All CVP subscale scores were lower (P < 0.01) in Group 1 than in Group 2 fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…After 40 min from the bolus injection of 1 g of human endothelin-1, the peptide levels had steadied to an apparent plateau of 0.402 Ϯ 0.108 nmol/l. As a comparison, the basal levels in human circulation are ϳ0.003-0.004 nmol/l (34). Therefore, caution is warranted when planning experiments in teleost fish with the use of constant infusion of endothelin because of the apparent risk of accumulation of the peptide in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The assay procedure has been described in detail previously (28). Human endothelin-1 RIA were performed as described earlier (34).…”
Section: Expression and Purification Of Gst-nt-pro-scp Fusion Proteinmentioning
confidence: 99%
“…Under normal physiological circumstances, the major site of atrial natriuretic peptide synthesis is in the atria, but under pathophysiological conditions associated with chronic pressure or volume overload, ventricular atrial natriuretic peptide gene expression is also activated (Ruskoaho 1992). Plasma atrial natriuretic peptide has been shown to rise during acute dynamic exercise (Ruskoaho et al 1989;Schmidt et al 1990;Vuolteenaho et al 1992), but even a 55-week-long treadmill exercise does not increase Author for correspondence: Ilkka Pörsti, Medical School, University of Tampere, Department of Pharmacological Sciences, FIN-33014 Tampere, Finland (fax π358 3 215 6170, e-mail ilkka.porsti /uta.fi).plasma atrial natriuretic peptide at rest, or the gene expression of atrial natriuretic peptide in the ventricles of normotensive dogs (Mäntymaa et al 1994). In contrast, endurance training for 31 weeks elevates both the content and gene expression of atrial natriuretic peptide in the ventricles of spontaneously hypertensive rats (Mäntymaa et al 1994;Sallinen et al 1996).…”
mentioning
confidence: 99%
“…Under normal physiological circumstances, the major site of atrial natriuretic peptide synthesis is in the atria, but under pathophysiological conditions associated with chronic pressure or volume overload, ventricular atrial natriuretic peptide gene expression is also activated (Ruskoaho 1992). Plasma atrial natriuretic peptide has been shown to rise during acute dynamic exercise (Ruskoaho et al 1989;Schmidt et al 1990;Vuolteenaho et al 1992), but even a 55-week-long treadmill exercise does not increase Author for correspondence: Ilkka Pörsti, Medical School, University of Tampere, Department of Pharmacological Sciences, FIN-33014 Tampere, Finland (fax π358 3 215 6170, e-mail ilkka.porsti /uta.fi).…”
mentioning
confidence: 99%